2020
DOI: 10.1111/1753-0407.13129
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal hormonal factors before menopause and incident type 2 diabetes in women: A 22‐year follow‐up of 83 799 women from the E3N cohort study

Abstract: Background In many populations the incidence of type 2 diabetes is higher in men than in women. This may be explained by exposure to female gonadal hormones, but so far, there is no consensus on their role over the life course in type 2 diabetes etiology. Methods Data are from 83 799 French women from the E3N (Etude Épidémiologique de Femmes de la Mutuelle Générale de l'Education Nationale) cohort study, followed for 22 years. Multivariable Cox models including classical risk factors were used to estimate haza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…In both cross-sectional [ 16 ] and longitudinal studies [ 17 , 18 ], earlier menopause was found to be associated with increased odds of diabetes. Recent cohort studies also reinforced the inverse association with observations that later menopause was associated with lower risk of diabetes [ 19 , 20 ]. However, in contrast, some authors reported that women who had later menopause experience were more likely to have diabetes [ 12 , 21 ].…”
Section: Introductionmentioning
confidence: 73%
“…In both cross-sectional [ 16 ] and longitudinal studies [ 17 , 18 ], earlier menopause was found to be associated with increased odds of diabetes. Recent cohort studies also reinforced the inverse association with observations that later menopause was associated with lower risk of diabetes [ 19 , 20 ]. However, in contrast, some authors reported that women who had later menopause experience were more likely to have diabetes [ 12 , 21 ].…”
Section: Introductionmentioning
confidence: 73%
“…On the other hand, chronic hyperglycemia of early onset T2DM and type 1 diabetes mellitus (T1DM), which is commonly presented at younger age, accelerate ovarian ageing. In the French prospective cohort study (83,799 women, 22 years of follow-up), later age at menopause was related to reduced T2DM risk [ 24 , 25 ]. A prospective analysis of the Women’s Health Initiative (WHI) data ( n = 124,379) showed that women with shorter (< 30 years) and longer (> 45 years) reproductive lifespan had an increased risk of T2DM (37% and 23%, respectively) [ 26 ].…”
Section: Menopausal Age and T2dmmentioning
confidence: 99%
“…Type 2 diabetes mellitus (T2DM) is one of the primary causes of death and CVDs in the world ( 95 ). At present, the correlation between ANM and T2DM is controversial ( 96 99 ). The inconsistencies in the results are possibly caused by variations in variable adjustment, ethnicity diversity in the sample population, or genetic traits.…”
Section: Anm As An Exposurementioning
confidence: 99%